1977
DOI: 10.1203/00006450-197707000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Fetal Lung Phosphatidyl Choline Synthesis by Cortisol: Role of Glycogen and Glucose

Abstract: Cortisol lung fetus maturation glucose phosphatidyl cholinc glycogcn surfactant Regulation of Fetal Lung Pllosphatidyl Choline Synthesis by Cortisol: Role of Glycogen and Glucose 'I'\renty pregnant rabl~its \\ere stutlietl in pairs. 1l:llf \rere ~i v e n cortisol subcutaneously on clays 24. 25, ancl 26 of gestation in (losage of 2 nig/lig/tlay. Ilalf scrvctl as controls aricl receivetl line. I'IIc fetal I111igs \\ere s t~~d i e d on the 27111 tlaj of gest:~tio~~ by incul):~ting lulig slices in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
1
1

Year Published

1980
1980
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 0 publications
4
27
1
1
Order By: Relevance
“…Nevertheless, hormones that accelerate lung Abbreviations maturation and stimulate surfactant production in the fetus also promote glycogen depletion (1). Glucocorticoids decreased lung T3, triiodothyronine glycogen in vivo in the fetal rabbit (17,18) and mouse (19) while RDS, respiratory distress syndrome dexamethasone and thyroxine had a similar effect in cultured fetal rat lung explants (20). The influence of a combination of these two hormones on this parameter of lung maturation, however, has not previously been reported.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Nevertheless, hormones that accelerate lung Abbreviations maturation and stimulate surfactant production in the fetus also promote glycogen depletion (1). Glucocorticoids decreased lung T3, triiodothyronine glycogen in vivo in the fetal rabbit (17,18) and mouse (19) while RDS, respiratory distress syndrome dexamethasone and thyroxine had a similar effect in cultured fetal rat lung explants (20). The influence of a combination of these two hormones on this parameter of lung maturation, however, has not previously been reported.…”
mentioning
confidence: 65%
“…Although glucocorticoids (17)(18)(19)(20), thyroid hormone (20), estrogen (44,45), and aminophylline (46,47) have previously been reported to accelerate the normal developmental decrease in lung glycogen, an acceleration of the earlier increase in lung glycogen was reported in only one previous study. Alescio and Dani (48) reported that the glycogen content of 1 1-day fetal mouse lung explants was increased when cultured in the presence of cortisol for 48 h. Effects of hormones on fatty acid synthesis in developing fetal lung have not been extensively examined.…”
Section: Discussionmentioning
confidence: 88%
“…It has been reported elsewhere (12) that in fetal rat lung explants 17P-estradiol decreased lung glycogen although the effect was much less marked than in the present study. Glucocorticoids also decrease lung glycogen both in fetal rabbits in vivo (8,34) and in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…In comparing results from investigations conducted by this laboratory and others on lung maturation, a number of noteworthy similarities were found between the effects of estrogen and glucocorticoids. Both accelerate morphologic maturation of the fetal lung (18) and deplete its glycogen content (8,34). Both increase the amount of phosphatidylcholine as well as the phosphatidylcho1ine:sphingomyelin ratio in lung lavage and increase the rate of choline incorporation into phosphatidylcholine in lung slices (33).…”
Section: Effect Of I7p-estradiol On Fetal Rabbit Lung and Liver Glycomentioning
confidence: 99%
“…44). fhese maturational processes-the ialI & pu&onary glycogen; the rise in surfactant svnthesis, and the amearance of lamellar bodies-are all accelerated by the admini'siration of exogenous glucocorticoids (14,23,29,31,32). In a retrospective analysis, Robert et al (3 1 ) showed that infants of diabetic pregnancies have a 5.6 times greater risk of developing the respiratory distress syndrome than those of nondiabetic gestations.…”
mentioning
confidence: 99%